INCREASING HUMAN SECURITY TO PREVENT WATER WARS IN THE FERGHANA VALLEY - SAKEEVA, Venera (CENTRAL ASIA AND THE CAUCASUS, 2013)
The Ferghana Valley is shared by three Central Asian republics of Kyrgyzstan, Uzbekistan, and Tajikistan. Largely agrarian, the communities residing in the area are heavily dependent on the availability of water for irrigation. As a result of Soviet-backed imaginary border removal and the creation of new borders, the communities became highly vulnerable to state policies and are challenged in establishing relations with each other. The deteriorated environmental conditions, such as dry climate and drought, have only fueled the competition among households to ensure their access to the scarce water resources. Without timely and comprehensive intervention strategies, the region can be compared to a time bomb that could have irreversible consequences. This article will examine the water problem in the Ferghana Valley from the perspective of a human security approach. In particular, it will analyze the trilateral spurious relations among environmental, economic, and community insecurities derived from the scarcity of water resources and lack of comprehensive water management strategies. To elaborate, it will look into how environmental insecurity has multidimensional impacts on economic and community security in the Ferghana Valley. This research with go on to identify the existing approaches to addressing the aforementioned issues and will scrutinize them to see whether or not they address human security of the communities residing in the Ferghana Valley. Subsequently, the article will propose an alternative solution that meets the principles of human security-friendly policies and will discuss strategies to improve alternative intervention within the framework of “do no harm.”